Difficulties in Monitoring Conspecifics Mediate the Effects of Visual Obstruction on the Level and Synchronization of Vigilance - Beauchamp, Guy (Frontiers in Ecology and Evolution, 2017)
For prey species that visually monitor their surroundings for signs of danger, obstruction in the field of view is expected to increase vigilance against predators. However, visual obstruction could also make it more difficult to monitor neighbors, which might increase vigilance on its own and also reduce the widespread ability to synchronize vigilance with neighbors. To address these issues, I performed an experiment in which the ability to monitor neighbors in chickens (n = 14) was prevented by visual obstruction while the ability to monitor predators was maintained for some group members but not for others. Vigilance increased with visual obstruction, but remained at the same level for foragers prevented from monitoring neighbors and predators and those only prevented from monitoring neighbors. This suggests that the increase in vigilance with visual obstruction was caused by the inability to monitor neighbors rather than predators. Synchronization of vigilance between group members also decreased in the visual obstruction treatment, suggesting that visual cues from neighbors rather than external cues are important to synchronize vigilance. The ability to visually monitor neighbors is thus an important determinant of the level of vigilance maintained by a prey species, and also an important factor in the synchronization of vigilance between neighbors.